The media's role in the consolidation of democracy in South Africa: the case of the SABC's soap operas as a cultural public sphere - Afrika, Lefa G (Centre for Film and Media Studies, 2022)
This study has been inspired by the political events in the past few years that signalled a general decline, instead of consolidation, of democracy in South Africa. The decline has caused a rising trust deficit between the government and the citizens of South Africa. These events have raised questions of the role of the media in the consolidation of democracy. Katrin Voltmer's pioneering work, The Media in Transitional Democracies (2013) shines an important light in delineating the role of the media in transitions, including democratic consolidation. Much of the focus of scholastic research in the subject of media and democracy has been on news and journalistic content. Jurgen Habermas' seminal work, The Structural Transformation of the Public Sphere (1989) also accorded more weight to the rational and cognitive, as opposed to the affective and emotive aspects of the media when arguing in favour of emancipatory potential of the public sphere. The rational and cognitive aspects are generally associated with news and journalistic content (McGuigan, 2005: 430). Unlike Habermas, this study follows the lead by scholars like Van Zoonen (2006) and McGuigan's (2005) interest in the popular entertainment content which has often been regarded as having little significance in politics, especially democracy. In its emphasis on the consolidation aspect of South African democratic transition, the study is conducted against the backdrop of the broader ‘third wave' transitions of the early 1990's (Huntington, 1991). The study's theoretical framework is aligned with Christians et al.'s (2009) revision of the Four Theories (Siebert, et al, 1956) of the press. Their approach is useful because of its normative strength that opens the possibilities of media roles in democratization. The normative approach allows a free exploration of the potential of the media, instead of restricting the media to the political systems within which they operate. In addition, it aligns itself to Jim McGuigan's theory of the cultural public sphere which highlights the often-ignored political potency of popular cultural texts in the public sphere. McGuigan (2005: 430) argues that the affective or emotive aspects of popular cultural texts enhance, rather than hinder, the quality of political engagement in the public sphere. Through entertainment television programmes, democratic ways of life can be portrayed as part of everyday, ordinary life (Stevenson, 2010: 276). Against the widely held expectation that the media should play a positive role in democracies, some scholars have noted that in reality, “this is not necessarily so” (Jebril, Stetka & Loveless, 2013: 3). Rather, the media can serve dictatorships as happily as they serve democracies (Voltmer, 2013: 23). Using the case studies of two soap operas of the South African Broadcasting Corporation (SABC), Muvhango and 7de Laan, the study explores the role of popular media in the enhancement or consolidation of democracy, and the circumstances under which this is carried out. The media of interest for this study is public service broadcasting (PSB). For most democracies of the third wave, especially in Africa, PSB has been an easy victim of political power. Because of its dependence on the state, PSB tends to be more susceptible to political interference than other media types. Like other PSBs, the SABC has clearly spelt-out objectives that are linked to the national developmental objectives, including the goal of promoting and deepening democracy. This connection makes it possible to evaluate the selected entertainment case studies against these objectives. The study uses Multimodal critical discourse analysis (MCDA) because it allows for the analysis of text in its multimodal form such as visuals and audio. It equally allows for the application of analytical tools borrowed from film and television theories. By indirect measurement, MCDA model is used in the study to evaluate how democracy is represented (promoted, negated, omitted) in various aspects of the text.